KEMAMPUAN MENGENAL HURUF VOKAL ANAK TUNAGRAHITA MELALUI MEDIA GAMBAR - Hasniati - Hasniati (Universitas Negeri Padang, 2013)
The background of this research is the discovery of two students grade D3 mild mental retardation / C who have difficulty in identifying vowels during follow lessons, this is because only classroom teachers use the lecture method and gave the task of reading to children. In other circumstances at the time of reading the words that have vowels [a, i, u] children experience difficulties because children do not know these vowels. The purpose of this research is to improve the ability to recognize vowels through media images for mild mental retardation children grade D3 / C. Type of research is a classroom action research (classroom action research) that takes the form of collaboration. These actions were taken to two children D3 grade mild mental retardation / C in SLB YAMIK shadow.The results showed for the first cycle held four meetings in the learning process that starts from mentioning letters, shows, reading the word, and the assessment of the work of children. Based on the average value obtained by the students at the end of the first cycle can be seen that the CH before the given action I get a value of 20% of all the indicators are given. And after a given action I got 40%. While NS before given action I got 15% of all the indicators are given. After the action I was given to 50%. In the second cycle performed in the learning process TN four times scored 60% on the implementation of the second cycle and NS got 80%.The results of the third cycle shows the results ability CH gets a score of 70% while the NS got 60%. From the results presentation and analysis of the data it can be concluded that the use of a picture card media can enhance the ability of the child to know vokali letter grade D3 mild mental retardation / C. Thus it can be suggested to the schools, teachers, and researchers can use the following for a picture card media to improve their children recognize vowels for mild mental retardation